2021
DOI: 10.3389/fmed.2021.691618
|View full text |Cite
|
Sign up to set email alerts
|

Serum Troponin T Concentrations Are Frequently Elevated in Advanced Skin Cancer Patients Prior to Immune Checkpoint Inhibitor Therapy: Experience From a Single Tertiary Referral Center

Abstract: Immune checkpoint inhibitor (ICI) therapy has revolutionized the treatment of several human malignancies, particularly metastatic skin cancer. However, immune-related myocarditis (irM), an immune-mediated adverse event (irAE), is often fatal. In the absence of a reliable biomarker, measurement of pre-ICI therapy serum troponin concentration has been proposed to identify patients at risk of developing irM, although real-world studies examining this strategy are lacking. Thus, we retrospectively analyzed the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
6
0
2
Order By: Relevance
“…Furthermore, pre-ICI TTEs were not investigated and TTEs during treatment were performed at different time points. Kurzhals et al retrospectively analyzed pre-treatment hs-TnT levels in 47 patients who subsequently received ICI therapy for locally advanced and/or metastatic melanoma [47]. One patient, who had normal pre-treatment hs-TnT, developed myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pre-ICI TTEs were not investigated and TTEs during treatment were performed at different time points. Kurzhals et al retrospectively analyzed pre-treatment hs-TnT levels in 47 patients who subsequently received ICI therapy for locally advanced and/or metastatic melanoma [47]. One patient, who had normal pre-treatment hs-TnT, developed myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Finke et al ( 32 ) recently reported that high levels of circulating cardiac troponin-T before starting chemotherapy predicted all-cause mortality after adjusting to glomerular filtration rate, age, gender, hypertension, diabetes, and adiposity, in which 86.7% (806 of 930) patients having a left ventricular ejection fraction > 50%. Prior cardiovascular disease, co-morbidity, hemodynamic instability, and pro-inflammatory cytokines produced from cancer cells damaged myocardial cells might affect the circulating cardiac troponin-T level ( 13 , 14 , 33 , 34 ). Assessment of troponin-T helps to identify patients with cardiotoxicity during cancer therapy ( 35 ), and preventative therapy with β-blocker and angiotensin converting enzyme inhibitor/angiotensin II receptor blocker were associated with less cardiac troponin-T elevation in cancer patients ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the circulating troponin-T levels in the peripheral blood were not evaluated at the time of tumor resection/biopsy, this study suggests a considerable attention may need to interpretate the cardiac troponin-T levels in the serum of cancer patients; circulating troponin-T from the tumor tissue may give false diagnosis of myocardial injury ( 16 ). However, it is noted that serum cardiac troponin-T level can be elevated with pre-existing/subclinical cardiac or noncardiac disorders without manifested cardiac dysfunction, meanwhile apparent normal cardiac function with elevated cardiac troponin-T cannot deny the presence of latent myocardial injury ( 34 , 37 ). We observed TNNT2 positive staining regardless of presence (+) or absence (-) of cardiovascular comorbidities (CVM): TNNT2(-)/ CVM(-), 13; TNNT2(-)/ CVM(+), 30; TNNT2( + )/ CVM(-), 14; TNNT2( + )/ CVM(+), 11 in 68 cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma was reported to be the second most frequent cancer associated with cardiac metastases, after mesothelioma, so the progression of the disease and heart failure related to increasing after-load should be always taken into consideration [ 83 , 84 ]. Also, Kurzhals et al (2021) reported elevations of serum troponin T levels in 28% of patients with advanced skin cancer prior to the beginning of the therapy, and the pre-therapeutic elevated troponin T concentrations were not associated with the development of myocarditis [ 85 ]. However, if and how the extent to which metastatic melanoma per se is associated with increased serum troponin T concentrations needs to be confirmed in larger studies.…”
Section: Review and Discussionmentioning
confidence: 99%